Effects of resveratrol, raloxifene, tibolone and conjugated equine estrogen on vaginal squamous cell maturation of ovariectomized rats - Hascalik, S; Celik, O; Tamser, M; Mizrak, B (Karger, 2005)
Objective: The effects of estrogen replacement therapy, selective estrogen receptor modulators, or tibolone on vaginal squamous cell maturation in postmenopausal women are not well established. Resveratrol ( 3,5,4'- trans - trihydroxystilbene) has been shown to bind the estrogen receptor in rat uteri. The aim of this study was to cytologically evaluate vaginal smears from ovariectomized rats treated with resveratrol, raloxifene, tibolone and conjugated equine estrogen, and to compare each drug with regard to vaginal epithelial maturation. Material and Methods: Forty-two bilaterally ovariectomized Wistar albino rats were equally randomized into 6 groups: ( 1) control sham-operated rats; ( 2) ovariectomized rats administered 0.1% ethanol; ( 3) ovariectomized rats administered resveratrol at a dose of 5 mg/kg/day p. o.; ( 4) ovariectomized rats administered conjugated equine estrogen (CEE) at a dose of 0.1 mg/kg/day p. o.; ( 5) ovariectomized rats administered tibolone at a dose of 0.25 mg/kg/ day p.o., and ( 6) ovariectomized rats administered raloxifen at a dose of 1 mg/kg/day p. o. Administration of drugs started 5 days after bilateral ovariectomy and continued for 35 days. After 35 days of treatment a vaginal smear was obtained from each rat. Smears were stained with the usual Papanicolaou method, and observed with a light microscope by an experienced cytopathologist. Cytological grading was made according to the extent of parabasal, intermediate, superficial and anuclear squamous cells. Results: Ovariectomized rats had lower scores for superficial and anuclear cells when compared to sham-operated rats ( p < 0.05). The CEE group had higher scores for superficial and anuclear cells than those of the ovariectomized, raloxifene and tibolone groups ( p < 0.05). The resveratrol-treated rats had higher scores for superficial cells but lower scores for parabasal cells than ovariectomized rats ( p < 0.05). The raloxifene and tibolone groups had the same scores for intermediate, superficial and anuclear cells but lower scores for parabasal cells compared to ovariectomized rats. Conclusion: The results of our study suggest that resveratrol offsets the reduction in vaginal stratification generally observed after oophorectomy. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: estrogen replacement therapy; squamous cell maturation; resveratrol; raloxifene; tibolone; equine estrogen, conjugated